Should Children with Auditory Processing Disorders Receive Services in Schools? - Lucker, Jay R. (Journal of the American Academy of Special Education Professionals, 2012)
Many children with problems learning in school can have educational deficits due to underlying auditory processing disorders (APD). For these children, they can be identified as having auditory learning disabilities. Furthermore, auditory learning disabilities is identified as a specific learning disability (SLD) in the IDEA. Educators and professionals accessing children for learning problems often do not understand or accept that there are such things as auditory processing deficits or APD. This paper presents a tutorial discussion of what are APDs, how they can affect children in schools, and how they should be assessed.